The Day after tomorrow - Emmerich, Roland (Pasig City : Viva video, 2004)
From the director of "Independence Day" comes a spectacular roler-coaster, ride that boasts pulse-pounding action and sensational mind-blowing special effects, When global warming triggers the onset of a new ice age, tornaddes flatten los Angeles, a tidal wave engulfs New York City and the entire Northern hemisphere begins to freeze solid. Now, climatologist Jack Hall (Dennis Quaid), His son Sam (Jack Gyllenhaal) and a small band of survivors must ride out the growing superstorm and stay alive in the face of an enemy more powerful and relentless than any they've ever encountered: mother nature!